Answer:
6cm
Explanation:
Given
12J to stretch from 8cm to 10cm ---- Expression 1
Additional 48J from 10cm to 14cm ---- Expression 2
Let l represents the length of the spring
Let k represent string constant,
We can then write ( from expression 1)
12 = integral of kx dx
The lower bound being 8 - l
And the upper bound being 10 - l
Integrating kx dx
We have
½kx²
= ½k[x²]
= ½k[(10 - l)² - (8 - l)²].
So, 12 = ½k[(10 - l)² - (8 - l)²] ------ Equation 1
From expression 2, we can write
48 = integral of kx dx
The lower bound being 10 - l
And the upper bound being 14 - l
Integrating kx dx
We have
½kx²
= ½k[x²]
= ½k[(14 - l)² - (10 - l)²].
So, 48 = ½k[(14 - l)² - (10 - l)²] ------ Equation 2
Divide Equation 2 by Equation 1, so we get
48/12 = ½k[(14 - l)² - (10 - l)²] / ½k[(10 - l)² - (8 - l)²] ----- ½k cancel out ½k
So, w have
4 = [(14 - l)² - (10 - l)²] / [(10 - l)² - (8 - l)²]
Recall that a² - b² = (a + b)(a - b).
So,
4 = [(14 - l - 10 + l) (14 - l + 10 - l)] / [(10 - l - 8 + l) (10 - l + 8 - l)]
4 = [(4)(24 - 2l)]/[(2)(18-2l)]
4 = (96 - 8l)/36 - 4l) ---- Multiply both sides by 36 - 4l
4(36 - 4l) = 96 - 8l
144 - 16l = 96 - 8l ----- Collect Like Terms
144 - 96 = 16 - 8l
48 = 8l ----- Divide both sides by l
48/8 = l
6 = l --- Rearrange
l = 6
So, the natural length of the string is 6cm